A Diagnostic Conundrum: Cerebral Radiation Necrosis Masquerading as Tumor in the Contralateral Hemisphere - Daljit, Tanshi; Miglani, Saarthak; Singh, Daljit; Saran, Ravindra K. (Indian Journal of Neurosurgery, 2025)
Cerebral radiation necrosis (CRN) is a recognized late complication following cranial irradiation. This article describes a unique case of CRN occurring contralaterally to the original irradiation site in a male treated for atypical meningioma with surgery and subsequent radiation therapy. This case highlights the diagnostic challenge of differentiating CRN from tumor recurrence or progression and highlights the importance of advanced imaging techniques and biopsy for diagnosis.
Keywords: cerebral radiation necrosis; contralateral cerebral radiation necrosis; radiation-induced brain necrosis